Answer:
The solution to these two equations is (3, 1)
Explanation:
So for the elimination method, we are basically multiply each equation by a factor that would allow us to cancel them out..
We could rewrite the equations as the following to make the elimination method easier:
-2y + 3x = 7
y + 4x = 13
We could multiply the second equation by positive 2 in order to cancel out the y from the first equation when we add.
-2y + 3x = 7
2y + 8x = 26 ---> Now we have 11x = 33, when we simplify, we have x = 3.
Now to find our y value in order to find the solution, we would just plug in our x value and solve for y. **We can use either equation to find the answer for this...
-2y + 3x =7.
-2y + 3(3) = 7
-2y + 9 = 7
-2y = -2
y = 1.
We can double check our answer by plugging in both x and y values into the second equation.
4(3) + 1 = 13.
12 + 1 = 13, so we are correct.
The solution to these two equations is (3, 1)